Nusinersen corrects L-arginine deficiency in the cerebrospinal fluid of patients with severe spinal muscular atrophy - Amber Hassan; Raffaella di Vito; Anna Caretto; Tommaso Nuzzo; Adele D'Amico; Chiara Panicucci; Claudio Bruno; Enrico Bertini; Alessandro Vercelli; Marina Boido; Francesco Errico; Livio Pellizzoni; et al. (Neurobiology of Disease)
Spinal Muscular Atrophy (SMA) is a progressive neuromuscular disorder caused by homozygous loss of the survival motor neuron 1 (SMN1) gene, leading to reduced SMN protein expression. Increasing evidence implicates neurotransmission deficits in the pathophysiology of SMA. In particular, alterations in neuroactive amino acids involved in glutamatergic neurotransmission have recently been identified in both the cerebrospinal fluid (CSF) of SMApatients and the spinal cord of SMNΔ7 mouse models. L-arginine, a precursor of nitric oxide, plays a critical role in glutamatergic receptor signalling, influencing neurotransmitter release, synaptic plasticity, and neuroprotection. However, it remains unclear whether SMN deficiency affects L-arginine metabolism in SMA. To address this, we used high-performance liquid chromatography to investigate whether SMN deficiency alters L-arginine homeostasis in the central nervous system of SMNΔ7 mice and in the CSF of SMA patients with varying disease severity, both before and after treatment with the SMN-inducing therapy Nusinersen. Notably, we observed significantly reduced L-arginine levels in the brainstem and spinal cord of symptomatic SMA mice compared to age-matched wild-type littermates. Consistent with these findings, we revealed lower L-arginine levels in severe SMA1 patients compared to milder SMA2 and SMA3 patients and healthy controls, enhancing the translational strength of our findings. Importantly, Nusinersen-mediated SMN upregulation fully restored L-arginine homeostasis in the CSF of severe SMA1 patients. In conclusion, our results demonstrate a dysregulation of L-arginine in SMA and highlight a role for SMN-enhancing therapies in restoring neurochemical alterations observed in patients with this neurodegenerative disease.